Whale-watching contributions for the study of cetacean-cephalopod interactions - Suciu, Stéphanie R. A. (2021)
Cephalopods are the primary source of food for several species of odontocetes. The unstable nature of this trophic resource is likely to affect the ecology of their cetacean predators. This can be reflected in whale conservation status but also in the tourist activities which focus on cetacean observation. However, the study of cetacean-cephalopod interactions is limited by the complicated and heavy logistics of dedicated scientific campaigns. Fortunately, this limitation can be overcome by coupling modern molecular tools with indirect sampling methods. In this note we present the first results of a project to involve whale watching companies, which represent an intense observation effort worldwide, in the collection of biological material and information for studies of cetacean-cephalopod interactions and cephalopod distribution. In early 2020 we contacted all whale watching companies on São Miguel Island, Azores. All of them welcomed the invitation and received training and a sampling kit. Nine cephalopod tissue samples were collected, most of them in close association with sperm whales. All samples were determined by DNA barcoding (confirmed in a few cases by morphological observation) to belong to the gelatinous giant octopod Haliphron atlanticus (Octopoda, Alloposidae). We believe that, although the Azores may have particularly favourable conditions for participatory science, similar programs can be replicated elsewhere.